Estudo da estimativa da carga máxima que uma estrutura de concreto pré-moldado suporta, utilizando a norma ABNT NBR 6118/2014 com base na norma ABNT NBR 6120/2019 - Marques, Laura Maira Penaforte de Oliveira (Universidade Federal Rural do Semi-Árido, 2021)
This work aims to estimate the loads acting on a precast concrete structure with two floors according to the recommendations of ABNT NBR 6120/2019, as well as to determine the maximum loading capacity of the structure of the building under study from the equations studied throughout the discipline of Strength of Materials and the dimensions of columns and beams measured in loco. For the development of the work, it was necessary to raise some data about the materials and elements of the building, enabling a determination of the maximum load that a structure support has, based on some reverse calculations to the design process. At the end, the results of the estimated loads according to the criteria of the ABNT NBR 6120/2019 standard and the results of the calculated loads based on the data collected were compared, noting that the discrepancy between the values was not large.
Keywords: Cargas; Estrutura de concreto pré-moldado; ABNT NBR 6120; Momento fletor; Compressão; Loads; Precast Concrete Structure; ABNT NBR 6120; Bending Moment; Compression; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA